Case Study On Jobstreet.Com Sdn Bhd And E-Recruitment Industry - Wan Sulaiman, Wan Kamarulfarid (2002)
The subject of this case study on JobStreet.com Sdn Bhd was triggered by the Malaysian economic situation where a lot of companies having difficulties to retain their workforce. These companies retrenched their employees to remain operational. In this situation where recruitment industry is considered employees' market, is it viable and profitable to manage a recruitment company with the use of Internet technology? This case study will provide valuable information on the e-recruitment industry and recruitment company's operation.